2019
DOI: 10.1289/ehp3860
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Effects of Fine Particulate Matter Exposure among Older Adults, during Wildfire and Non-Wildfire Periods, in the United States 2008–2010

Abstract: Background:The effects of exposure to fine particulate matter (PM2.5) during wildland fires are not well understood in comparison with PM2.5 exposures from other sources.Objectives:We examined the cardiopulmonary effects of short-term exposure to PM2.5 on smoke days in the United States to evaluate whether health effects are consistent with those during non-smoke days.Methods:We examined cardiopulmonary hospitalizations among adults ≥65 y of age, in U.S. counties (n=692) within 200km of 123 large wildfires dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
120
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 32 publications
6
120
0
2
Order By: Relevance
“…Despite removing wildfire days with extremely high PM2.5 concentrations, our results were similar to those of Deflorio-Barker et al [12], Reid et al [13], and Delfino et al [14], who all found that PM2.5 had a stronger association with asthma visits or hospitalizations during wildfire periods than during nonwildfire periods. We thus showed that the stronger associations of wildfire PM with asthma visits found in these studies cannot be solely attributed to differences in the concentration of wildfire PM and nonwildfire PM.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Despite removing wildfire days with extremely high PM2.5 concentrations, our results were similar to those of Deflorio-Barker et al [12], Reid et al [13], and Delfino et al [14], who all found that PM2.5 had a stronger association with asthma visits or hospitalizations during wildfire periods than during nonwildfire periods. We thus showed that the stronger associations of wildfire PM with asthma visits found in these studies cannot be solely attributed to differences in the concentration of wildfire PM and nonwildfire PM.…”
Section: Discussionsupporting
confidence: 90%
“…Our study used models very similar to those of Deflorio-Barker et al [12], Reid et al [13], and Delfino et al [14], which also included an interaction term between PM and an indicator for days affected by wildfire smoke. However, a key difference in our study is that we excluded wildfire days where PM2.5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A national study showed via principal component analyses that several vulnerability factors similar to those for general air pollution were relevant for fire-PM 2.5 ; specifically, factors included age (e.g., those >65 years); adults with respiratory disease (e.g., COPD and asthma); adults with hypertension, obesity and diabetes; children with asthma; and economic deprivation [35]. Age may also be a factor contributing to a population's susceptibility [36][37][38][39][40].…”
mentioning
confidence: 99%
“…Looking specifically at asthma, wildfire smoke has been linked to increases in severe asthma-related outcomes such as emergency department visits (B. L. Alman, 2014;Breanna L. Alman et al, 2016;Gan et al, 2017;Haikerwal et al, 2016;Hutchinson et al, 2018;Kolbe & Gilchrist, 2009;Prevention, 1999;Rappold et al, 2011), overall hospital visits (Churches & Corbett, 1991;Duclos et al, 1990;Gan et al, 2017;Johnston et al, 2002;Prevention, 1999;Reid, 2014), and emergency medication use (Caamano-Isorna et al, 2011;Elliott et al, 2013;Tse et al, 2015). Indeed, Deflorio-Barker et al recently found that asthmarelated hospitalizations among elderly Americans were more sensitive to ambient PM 2.5 on smoke days than on nonsmoke days (DeFlorio-Barker et al, 2019). However, there has been limited research relating wildfires to less-severe asthma outcomes.…”
Section: Introductionmentioning
confidence: 99%